Pelatihan Desain Modul Ajar Berdiferensiasi Bagi Guru-Guru SD Inpres 1 Tondo - I Nyoman Murdiana; Sukayasa Sukayasa; Muh Habi; Pathuddin Pathuddin; Fajriani Fajriani; Akhyar H.M. Tawil (Abimanyu : Jornal of Community Engagement, 2026)
Differentiated learning is one of the learning approaches in the implementation of the Independent Curriculum (IKM). Discussions with the principal of SD Inpres 1 Tondo during the guidance of the 8th Batch of Teaching Campus Students (August-December 2024) revealed that most elementary school teachers in the Tondo sub-district were unable to develop differentiated teaching modules. This community service activity was held on September 1, 2025, at SD Inpres 1 Tondo. The training participants consisted of teachers from SD Inpres 1 Tondo, SD Inpres 2 Tondo, SD LIK Layana, and SD Alkhairat Tondo, with a total of 30 participants. This community service activity aimed to provide understanding and practical knowledge to the participants so they could design differentiated teaching modules. The training methods used were presentations, discussions, and mentoring. Data was collected by giving individual assignments to create differentiated teaching modules for a topic to be taught. The collected data was analyzed using percentage analysis. Observations and Q&A sessions during the training indicated that participants were highly enthusiastic about participating, and all participants understood how to develop differentiated teaching modules. Data analysis revealed that the average participant's ability to develop differentiated teaching modules was very good, with a score of 86.67.